A new species of Gieysztoria (Platyhelminthes; Rhabdocoela; Dalyelliidae) from a freshwater lake in Queensland, Australia - Hochberg, Rick; Cannon, Lester R.g. (Zootaxa, 2001)
A new species of Dalyelliidae, Gieysztoria queenslandica, is described from a freshwater lake in Brisbane, Queensland, Australia. Gieysztoria queenslandica n. sp. is a member of the Aequales group of Gieysztoria and differs from its congeners by possession of an S-shaped ovary, a Y-shaped oviduct leading to a separate receptaculum seminis, and the shape and size of the male copulatory organ. The sclerotic male organ of G. queenslandica is characterized by 27-32 broad, dagger-like spines arising from a hollow crescent-shaped girdle. The new species is seasonally abundant (April- July) in an artificial lake present on the St. Lucia campus of the University of Queensland in Brisbane, Australia.